Enhancing trans-resveratrol topical delivery and photostability through entrapment in chitosan/gum Arabic Pickering emulsions - Sharkawy, Asma (2018)
The surfactant-free nature and higher stability of Pickering emulsions make them preferable solutions over conventional emulsions for skin applications. In this work, Pickering emulsions stabilized by chitosan/gum Arabic (CH/GA) nanoparticles were tested as vehicles for trans-resveratrol topical delivery. Skin absorption was examined ex vivo using Franz diffusion cells and porcine skin. Pickering emulsions allowed higher cutaneous retention and lower permeation of resveratrol, in comparison with a control solution based on a 20% v/v ethanol. The total amount of resveratrol retained in the skin, 24 h after the application, was 11.60% and 10.82% of the applied dose for the tested Pickering emulsion-based formulations prepared with 0.5% and 1.5%w/v CH/GA nanoparticles, respectively. In contrast, resveratrol skin retention from the control solution was only 2.86%. Confocal laser scanning microscopy revealed enhanced skin deposition of Nile Red to deeper layers from the Pickering emulsionbased formulations. Moreover, Pickering emulsions led to trans-resveratrol photostability increase, as measured after exposure to UV for 4 h. These results show that the CH/GA Pickering emulsions are promising solutions for the topical delivery of trans-resveratrol and have the potential to be used as green cosmetic products.